Is Liver Resection in Metastases of Exocrine Pancreatic Carcinoma Justified? - Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
No abstract available. Image: College of Physicians and Surgeons, Columbia University. New York, NY, USA